Dynamic Cycle of Low Back Pain: A 17-Year, Population-Based Study Analyzing the National Health Insurance Service Data in South Korea - Mi-Ran Goo; Deok-Hoon Jun; Do-Youn Lee (Medicina)
Background and Objectives: Low back pain (LBP) is a highly prevalent musculoskeletal condition that frequently recurs, leading to increased healthcare utilization and socioeconomic burden. While short-term management strategies are well-documented, long-term recurrence patterns remain insufficiently studied. This study aims to describe the long-term recurrence patterns and healthcare utilization associated with LBP in a nationwide cohort over a 17-year period. Materials and Methods: This descriptive, retrospective longitudinal cohort study utilized data from the Korean National Health Insurance Service (NHIS) database (2002–2018). We included 3,086,665 patients who sought medical care for LBP (ICD-10 code M54.5) at least once in 2010. Patients with a history of disability rating assessments were excluded. The primary outcomes included the number of LBP episodes, episode duration, recurrence patterns, and changes in healthcare utilization. We assessed the number of healthcare visits per episode and the interval between episodes over time. Results: Among the study population, 79.4% experienced recurrent LBP, with an average of 5.0 ± 4.9 episodes per patient. Recurrence rates increased with each episode. In addition, episode duration lengthened, and intervals between episodes shortened. Healthcare utilization also increased, with patients requiring more visits per episode over time. The demographic and socioeconomic characteristics of the LBP patients in our sample were also described. Conclusions: In this population-based sample, LBP follows a progressive course, with increasing episode frequency, prolonged duration, and escalating healthcare utilization over time. These findings highlight the need for early intensive management and long-term follow-up strategies to mitigate the growing burden of recurrent LBP on individuals and healthcare systems.